Confronting the "Enemy Within" Security Intelligence, the Police, and Counterterrorism in Four Democracies - Chalk, Peter (RAND Corporation, 2004)
Since the September 11, 2001, terrorist attacks, critics have charged that the Federal Bureau of Investigation, while qualified to investigate terrorist incidents after the fact, is not well equipped enough to adequately gather and assess information to prevent attacks. More intrinsically, many believe that given a predominant and deeply rooted law enforcement and prosecutorial culture, the bureau may not be able to change operational focus toward dedicated counterterrorism intelligence gathering and analysis. To better inform debate, researchers analyzed the domestic security structures of four allied countries--the United Kingdom, France, Canada, and Australia--weighing both their positive and negative aspects. (PW/PC)